Comparison of Different Methods for Separation of Haploid Embryo Induced through Irradiated Pollen and Their Economic Analysis in Melon (Cucumis melo var. inodorus). (29th May 2013) - Baktemur, Gökhan; Taşkın, Hatıra; Büyükalaca, Saadet
Abstract : Irradiated pollen technique is the most successful haploidization technique within Cucurbitaceae . After harvesting of fruits pollinated with irradiated pollen, classical method called as "inspecting the seeds one by one" is used to find haploid embryos in the seeds. In this study, different methods were used to extract the embryos more easily, quickly, economically, and effectively. "Inspecting the seeds one by one" was used as control treatment. Other four methods tested were "sowing seeds direct nutrient media, " "inspecting seeds in the light source, " "floating seeds on liquid media, " and "floating seeds on liquid media after surface sterilization." Y2 and Y3 melon genotypes selected from the third backcross population of Yuva were used as plant material. Results of this study show that there is no statistically significant difference among methods "inspecting the seeds one by one, " "sowing seeds direct CP nutrient media, " and "inspecting seeds in the light source, " although the average number of embryos per fruit is slightly different. No embryo production was obtained from liquid culture because of infection. When considered together with labor costs and time required for embryo rescue, the best methods were "sowing seeds directly in the CP nutrient media" and "inspecting seeds in the light source."